2001
DOI: 10.1524/ract.2001.89.8.519
|View full text |Cite
|
Sign up to set email alerts
|

The migration of radionuclides237Np,238Pu and241Am in a weak loess aquifer: A field column experiment

Abstract: The migration of radionuclidesThe water flow velocity in the experimental column was calculated as 1.15±0.05 cm/d. The activity distribution of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Early studies were made on the natural apatite whose results suggested some problems due to the dissolution of the materials with pH changes [3]. Due to their abundance in the geosphere, much attention has been paid to the aluminosilicates and clays with a view to finding suitable engineered barriers for radioactive wastes confinement [4,5]. Recently, phosphated derivates containing lanthanum, thorium and uranium have been also studied in order to produce stable materials with sorbent properties [6].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies were made on the natural apatite whose results suggested some problems due to the dissolution of the materials with pH changes [3]. Due to their abundance in the geosphere, much attention has been paid to the aluminosilicates and clays with a view to finding suitable engineered barriers for radioactive wastes confinement [4,5]. Recently, phosphated derivates containing lanthanum, thorium and uranium have been also studied in order to produce stable materials with sorbent properties [6].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments with trace amounts of radionuclides were performed in several underground research facilities (URF) [19][20][21], however, experiments with real vitrified radioactive waste were not yet performed in URF. Up to now, laboratory scale leaching and alteration tests is the only possibility to study complex interactions between the solidified waste, buffer, and host rock in static and dynamic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, WPT has found application in numerous fields at various voltage and power levels [1], [2], [3]. There are different methods used to transfer the power without use of wires based on distance between source and load.…”
Section: Introductionmentioning
confidence: 99%